Effect of bentonite on growth in crossbred calves fed diet containing urea - Mohini, Madhu; Singh, G P; Kewalramani, Neelam (The Indian Journal of Animal Sciences, 2012)
Crossbred calves (12) of 9 months age were divided into 4 groups of 3 animals each. Groups 1 and 2 animals were fed concentrate mixture, wheat-straw and maize-fodder. In groups 3 and 4, 1 % urea replaced the equal amount of nitrogen of GNC in concentrate mixture and rest of the feeding regimens were same. Groups 2 and 4 were given bentonite 2% of the concentrate mixture. Body-weight gain (kg) in 5 months was 110±7.57, 111±12.S0, 108±3.05 and 99.66±0.33 in groups 1, 2, 3 and 4, respectively (P>0.05). DMI kg/day and kg/ 100 kg bwt did not differ significantly in the treatment groups. Digestibility of DM, OM CP, EE and NFE was not affected among different groups. At the end of the experiment the body composition was estimated. No significant differences were observed among the 4 groups though there was less protein in urea fed groups. Therefore, this study indicated that inclusion of bentonite with of without urea did not have any significant effect on growth in crossbred calves.